DETERMINING THE OPTIMAL VERTICAL INDEX - Akhmadov Inomjon Nizomitdin; Abduqayumov Jamshidbek; Pardayeva Nodirabegim; Imomjonov Sardorbek; Ibodullayeva Shaxrizoda (Лучшие интеллектуальные исследования, 2024)
Annotation: There are some references in modern sources, mainly in the section of orthopedic dentistry, where the LVI index was used as a diagnostic tool for prosthetics.